Terapias pulpares conservadoras e regeneração pulpar- Uma nova era na endodontia: Análise laboratorial e série de casos - Oliveira, Lilian Vieira (2021)
The general objective was to evaluate in vitro, in models that mimic pulpotomies, staining and cytoxicity of biomaterials, and to present, through a case report, the feasibility and success of a regenerative endodontic procedure for the treatment of young molars. Objective 1: Simulate complicated coronary fracture in an incisor treated by total pulpotomy with Bio-C Temp (BC-Angelus) compared to two materials (MTA Flow – MTA, UltraCal XS-UC; Ultradent), evaluating tooth discoloration, radiopacity and cytotoxicity in pulp cells. Objective 2: Simulate partial pulpotomy with Bio-C Temp (BC) compared with Bio-C Repair (BCR-Angelus) and Biodentine (BD-Septodont), evaluating tooth discoloration, radiopacity, cytotoxicity. Objective 3: To report the follow-up of a series of revascularization cases in young permanent molars, with mechanized preparation of root canals. In objectives 1 and 2, bovine teeth were prepared to simulate extensive coronary fracture in a tooth with an open apex. The roots were filled with an agar / blood mixture, and the materials placed on it. The control group was filled with agar / blood only. Color evaluation analyzes were performed using a spectrophotometer. The total color change (ΔEab, ΔE00) and whiteness index (WI) were calculated based on CIELAB. Digital radiographs were acquired for radiopacity analysis. Human pulp cells were used to analyze cell viability. ANOVA and Tukey tests were used to compare the experimental groups, and Dunnett's for comparisons with the control. In total pulpotomies (objective 1) all materials were associated with discoloration values greater than acceptable and BT resulted in a color change that was less or similar to MTA and UC, respectively. A reduction in radiopacity was observed only in the MTA (P = 0.007). The cell viability of the materials was similar to that of the control (DMEM) (P> 0.05), except for BT which had significantly lower viability (P <0.001). In partial pulpotomies (objective 2), BCR showed greater radiopacity and less color change (ΔEab / ΔE00) than other materials (P <0.005; P <0.001). BD showed cell viability similar to that of the control at the lowest dilutions and BCR was similar to the control, regardless of the dilution (P> 0.05). The case series describes a modified revascularization technique in young permanent 11 molars. The patients were submitted to manual preparation, followed by rotating NiTi files and calcium hydroxide paste. In the second consultation, the intracanal medication was removed, with final irrigation with EDTA under ultrasonic agitation and promotion of the clot. Sealing with MTA and glass ionomer and restoration with resin. After 15 days, there was no pain, edema and fistula, closure of the root apex and reduced canal light. Based on the results of the three objectives, it was concluded that: (1) in total pulpotomies, BT had acceptable cell viability, similar to that of MTA and UC at higher dilutions, and BT resulted in less color change than MTA and UC; in partial pulpotomies BCR showed better results than BD and BCT, with less color change, greater radiopacity and viability> 80%; the findings from the case series confirm that endodontic regeneration after mechanized root canal preparation is a promising option for maintaining permanent molars in adolescents.